(untitled) (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
What was the catalyst behind the rushed exodus of tens of thousands of Jews from Yemen during the second and third phase of Operation Magic Carpet? What led to the exit that was unique in scope and speed compared to former waves of migration from Yemen, and which took place in contrast to the predictions of both the British and the organizers of the Aliyah, who expected the Jews to leave gradually over a period of several years? So far, this phenomenon was not emphasized within the research, and was explained away as the result of a combination of circumstances in real time, religious-messianic motives, and the practical advantages embedded within the foundation of the State of Israel. In this article, I will show that these explanations still leave a gap in our understanding of the broader picture of this mass immigration of Jews from Yemen, and that a satisfactory explanation for the question has yet to be provided. I will turn a spotlight on the harsh events that took place in Yemen during the year and a half before this wave of immigration, and examine their influence on the feelings of Jews, their living conditions, and their sense of security. A new reading of existing testimonies, including letters written by Yemenite Jews during the fact, as well as later testimonies, tells the story of these immigrants and of their departure and suggests that alongside the familiar push and pull factors, migration from Yemen also had clear elements of escape. I suggest that the series of difficult events that preceded migration and the weakening of the Imam’s protection spread continuing feelings of anxiety, and uncertainty among the Jews of Yemen, shaking the very foundations of their sense of security and pushing them toward extensive and urgent migration from Yemen to Israel – the only state that offered them sanctuary and hope for the future.